Can the World Monetary System be Saved from Collapse by Monetary Gold - Varlamova, S.; Medvedeva, M. (Journal of Reviews on Global Economics, 2018)
The world community is gripped by the expectation of significant changes in the international monetary system, which has been permanently in crisis for decades. The uncertainty of the future gives rise to a sense of impending catastrophe, which must be prepared now, finding reliable anchors for preserving capital and providing an equivalent exchange in commodity markets. Historically, during a period of aggravation of the crisis of the international monetary system, monetary gold invariably remains as a reliable anchor, which is due not only to its unique properties, but also to the mentality of economic entities of all levels. The article deals with the basis of the emergence and periodic aggravation of the crises of the international monetary system, the causes of the new exacerbation, and the changing role of monetary gold in the process of globalization of the world economy. The role of international reserves in the gold reserve in the maintenance of socio-political stability is shown, the reasons determining the need to preserve and increase the gold reserves of central banks are substantiated.